Validity, Reliability and Responsiveness of the Cognitive Exercise Therapy Approach-Biopsychosocial Questionnaire (BETY-BQ) in Knee Osteoarthritis - Bulut, Zeynep Irem; Unal, Edibe; Oksuz, Sevim; Dogru, Atalay; Akyol, Ahmet; Yakut, Yavuz (Springer Heidelberg, 2025)
PurposeThis study was planned to test whether the Cognitive Exercise Therapy Approach- Biopsychosocial Questionnaire (BETY-BQ) is an appropriate questionnaire in assessing the biopsychosocial status in KOA.MethodsFrequently used assessment tools, OA-specific scale The Western Ontario and McMaster Universities OA Index, the Hospital Anxiety and Depression Scale, and the Short Form-36 were utilized for the validity and responsiveness of BETY-BQ in individuals with KOA. The test-retest method, internal consistency analysis, and item analysis were used to test reliability. For the test-retest method, BETY-BQ was administered again to the same 30 individuals 1 week later. To assess the responsiveness of the BETY-BQ, individuals who underwent medical treatment were subjected to a second round of questionnaire administration after a 3-month interval.ResultsModerate to weak correlations between BETY-BQ and the other questionnaires ensued the divergent validity. According to the confirmatory factor analysis, all goodness-of-fit indices of BETY-BQ were acceptable (CMIN/df = 2.212; RMSEA = 0.080; SRMR = 0.08). Both Cronbach's alpha (0.900) and ICC value (0.941) showed that the BETY-BQ has excellent reliability in the KOA population. The Bland-Altman Plot showed high agreement as all differences between the first and second BETY-BQ were found between the 95% lower and upper limits. BETY-BQ demonstrated moderate responsiveness as the effect size and standardized mean response were 0.656 and 0.566, respectively.ConclusionA valid, reliable, responsive, multi-dimensional, and self-reported questionnaire for measuring biopsychosocial status in KOA was introduced to the use of healthcare professionals.
Keywords: Osteoarthritis; Biopsychosocial; Validity; Chronic pain; Function; Holistic